The effects of perceptual deprivation on exploratory and problem-seeking behavior of the albino rat. - Blank, Arthur M. (University of Ottawa (Canada), 1973)
This is a longitudinal study, having as its main purpose to determine the influence of environmental experience, specifically that of perceptual deprivation on problem-seeking behavior of rats. The effects of perceptual deprivation on exploratory behavior, and the distinctness of exploratory and problem-seeking behavior are also investigated. The subjects for the present study were sixty Sprague-Dawley albino rats. A three phase experimental procedure was utilized. In phase one pre-experimental measures were obtained from all subjects of their problem-seeking and exploratory behavior. Phase two, the experimental phase, consisted of dividing the animals into two groups and rearing them for thirty days in either a perceptually deprived or normal environment. During the third phase, all rats were post-tested on both the problem-seeking and exploratory measures. The major hypothesis tested states that the placement of animals in a perceptually deprived environment for a thirty day period will result in significant increases in both their problem-seeking and exploratory behaviors. Significant results were found and the hypothesis, therefore, was substantiated. A low but significant relationship was found to exist between problem-seeking and exploratory behavior indicating that the two behaviors do contain common elements. Eight minor hypotheses were also tested, attempting to determine the changes in exploratory or problem-seeking behavior of animals that have previously been divided into high or low groups according to either their problem-seeking or exploratory behavior and then reared in perceptually deprived or normal environments. Non-significant results were found in all but two cases. The results of the present investigation were interpreted in the light of the concept of optimal stimulation. Neurophysiological explanations were put forth indicating that the behavior changes due to the deprived rearing are dependent on neural changes, particularly in the reticular activating system.
Keywords: Biology, Animal Physiology.